Acquit Et De Charge to the Responsibilities of the Management of Limited Liability Companies - Aisyah, Rizka Rahadiyani; Prasetyo, Handoyo; Fahrozi, Muhammad Helmi; Surahmad, Surahmad (Budapest International Research and Critics University, 2021)
The form of a limited liability company is the most widely used form of economic activity today. In the General Meeting of Shareholders, the Managements and Commissioners in realizing the accountability for what they have done in one financial year, are obliged to submit an annual report. With the approval of the annual report responsibilities from the Board of Directors, the Managements gets